A study on factors that can contribute stress at the workplace among employees at Pelorus Intelligence and Technology Academy Sdn. Bhd. / Nurbaizura Amiruddin - Amiruddin, Nurbaizura (Faculty of Business and Management, 2010)
Work plays a central role in the lives of many people, and thus the impact of occupational stress is an important issue for both individual employees and the organizations in which they work. This report aims to investigate and identify the factors that can contribute stress among employees at Pelorus Intelligence and Technology Academy Sdn Bhd. This research will find whether stress’s factors such workload, interpersonal relationships and ergonomic factors. By using all items in Questionnaire, the findings highlight three factors that comprise Workload, interpersonal relationship and ergonomic factors. In determining the implication of stress factors towards employees at the workplace, a Likert-type scale has been developed and tested. Therefore, in this research, researcher tries to identify the implications of stress factors towards employees at the workplace.